FAKTOR-FAKTOR YANG BERPENGARUH DALAM PEMILIHAN METODE AKUNTANSI PERSEDIAAN - Tito Destafia, 13.05.52.0135; Puspitasari, Elen (Students Journal of Accounting and Banking, 2017)
This research examined the effect of firm size, the intensity of the inventory, inventory variability, variability in cost of sales, financial leverage, current ratio, and the structure of ownership of the selection inventory accounting method. This research was conducted at the Indonesian Stock Exchange by using analysis unit manufacturing companies that have gone public. The sampling method in this research using purposive sampling the study period of 2013 to 2015. The relationship and or influence between independent variables and the dependent variable is explained by using logistic regression analysis. The results of the study are as follows: the size of the company, variability in cost of goods sold, financial leverage, ownership structure significantly influence the selection method of inventory accounting, whereas the intensity of inventory, the variability of inventory, the current ratio does not significantly influence the selection method of inventory accounting.Keywords: Company Size, Intensity Inventory, Inventory Variability, Variability Of Cost of Goods Sold, Financial Leverage, Current Ratio, Ownership Structure, Selection Inventory Accounting Method